Stakeholders’ Perception of Causes and Consequences of ASUU Strike Among Public Universities in Nigeria: 1999–2022 - Aun Thompson Toryuha (Polish Political Science Yearbook)
One of the ways workers express their displeasure to their respective employers is through industrial action or strike, as it is commonly called. This study investigated the causes and consequences of the Academic Staff Union of Universities strike among public universities in Nigeria. The study employed the descriptive survey method. The population of the study comprised all the 91 public universities in Nigeria; the sample of the study was 400 stakeholders, comprising of lectures, students, parents, transporters, and marketers across all the public universities in the nation, who were selected using multistage sampling procedure of purposive and simple random sampling at their respective public universities. Four hundred respondents were sampled from twelve (12) universities, where 33 respondents were selected from each university. The data collection instrument for this study was a self-designed questionnaire titled “Stakeholders’ Perception of Prevalence, Causes, and Consequences of ASUU Strike among Public Universities in Nigeria: 1999-2022 (SPCCASPUN)”. The questionnaire was on a 5-point Likert scale containing 24 items, validated via experts/professionals with a reliability of 0.87 obtained using a split-half method. At the same time, the data was analyzed using descriptive and inferential statistics of mean rating, percentage, and t-test. Findings of the study revealed, amongst others, that poor budgetary allocation to the education sector, failure of the federal government to honor their long-term agreement, staff bonuses, the politicization of the ASUU strike, revitalization of universities, etcetera are causes of the ASUU strike. As identified by the stakeholders, the consequences include loss of interest in school due to increased social vices, the rush of academic programs, missing out on NYSC and other job opportunities, and loss of sponsorship, among others. It was concluded that both the government and ASUU should come to terms and resolve the issue once and for all to avoid future reoccurrence.